2020
DOI: 10.1259/bjrcr.20200026
|View full text |Cite
|
Sign up to set email alerts
|

A case series of thoracic dynamic contrast-enhanced MR lymphangiography: technique and applications

Abstract: Dynamic contrast-enhanced magnetic resonance lymphangiography is a radiation-free, high spatial resolution technique which is increasingly used to evaluate thoracic lymphatic disorders and for pre-procedural planning. DCE has the added advantage of allowing dynamic real-time evaluation of lymphatic flow. It can be employed to investigate commonly encountered clinical situations such as recurrent pleural effusions following trauma, thoracic duct injury after thoracic surgery, and exclude diseases and congenital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Dynamic contrast-enhanced magnetic resonance lymphangiography is a technique with high spatial resolution technique that does not involve the use of ionizing radiation and is increasingly used for evaluating lymphatic disease evaluation and preoperatively planning. 10 This method could have delineated the lymphatic reflux from the cisterna chyli.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic contrast-enhanced magnetic resonance lymphangiography is a technique with high spatial resolution technique that does not involve the use of ionizing radiation and is increasingly used for evaluating lymphatic disease evaluation and preoperatively planning. 10 This method could have delineated the lymphatic reflux from the cisterna chyli.…”
Section: Discussionmentioning
confidence: 99%
“…It is non-invasive, safe, and simple. It provides dynamic information, but its spatial resolution and anatomic details are lacking [ 10 ]. Using rigid cystoscopy to demonstrate chyle efflux from the ureteric orifice helps determine which side the chyluria originates from.…”
Section: Discussionmentioning
confidence: 99%
“…The studies we reviewed on this topic all reported a successful execution of contrast-enhanced MR lymphangiography in pediatric patients as well as adults, and even lead to changes in the treatment approach of some cases [7][8][9]. For the ideal visualization of the central lymphatic system, a combination of T2 weighted MR and contrast-enhanced MR lymphangiography is recommended [10].…”
Section: Imagingmentioning
confidence: 99%
“…Về tổng thời gian chụp cộng hưởng từ bạch mạch hiện chưa có nghiên cứu thống kê cụ thể để so sánh với kết quả của chúng tôi. Năm 2020, tác giả Lee và cộng sự có nhắc đến thời gian thực hiện kỹ thuật chụp tính từ khi bệnh nhân được cho vào máy chụp là khoảng 30 phút [6].…”
Section: Hình 1 Chọc Hạch Bẹn Dưới Hướng Dẫn Siêu âM Vị Trí đầU Kim N...unclassified